2011
DOI: 10.1007/s11046-011-9456-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profiling of the Dimorphic Pathogenic Fungus, Sporothrix schenckii

Abstract: Sporotrichosis is a common cutaneous mycosis caused by the dimorphic fungus Sporothrix schenckii, which exhibits a temperature-dependent dimorphic switch. At 25°C, it grows in a mycelial phase, while at 37°C, it forms unicellular yeast cells. The formation of yeast cells was thought to be a requisite for the pathogenicity of S. schenckii. To identify fragments that might be related to morphogenesis, whole-cell proteins from the mold and early yeast stages of S. schenckii were analyzed using 2DE. Among thousand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…We previously reported differentially expressed genes between the mycelial and the yeast phases of S. schenckii using 2DE. The expressed sequence tag of spotC homologous to the DRK1 histidine kinase from B. dermatitidis clearly increases in the yeast form of S. schenckii (4).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported differentially expressed genes between the mycelial and the yeast phases of S. schenckii using 2DE. The expressed sequence tag of spotC homologous to the DRK1 histidine kinase from B. dermatitidis clearly increases in the yeast form of S. schenckii (4).…”
Section: Introductionmentioning
confidence: 99%
“…The question remains of whether SsSir2 has the same function in the phenotypic switching of S. schenckii similar to the Sir2 ortholog in other dimorphic fungi. In our previous study, the SsSir2 protein expression level in yeast cells was found to be 5.47-fold higher than that in the mycelial phase of S. schenckii (6). In this study, the mRNA expression of SsSte20 in yeast cells of both ATCC10268 and a clinical S. schenckii isolate from a patient with fixed sporotrichosis (data not shown) were higher than in the mycelial ones.…”
Section: Discussionmentioning
confidence: 84%
“…In a recent study of ours, differentially expressed proteins altered by phenotypic switching in S. schenckii were identified using two-dimensional electrophoresis. One of these proteins is homologous to the Sir2 protein from Aspergillus fumigatus and its expression increases in the early yeast form of S. schenckii (6). …”
Section: Introductionmentioning
confidence: 99%
“…This group also demonstrated an upregulation of the Hsp70 chaperone Hsp88 in the development of the yeast phase of Spor. schenckii at 37 u C; however, the precise role the hsp88 gene remains unclear (Zhang et al, 2012).…”
Section: Dimorphismmentioning
confidence: 99%